Ferroptosis in non-alcoholic liver disease: Molecular mechanisms and therapeutic implications - Cheng, Zilu; Chu, Huikuan; Zhu, Qingjing; Yang, Ling (Frontiers in Nutrition, 2023)
Ferroptosis refers to a novel modality of regulated cell death characterized by excessive iron accumulation and overwhelming lipid peroxidation, which takes an important part in multiple pathological processes associated with cell death. Considering the crucial roles of the liver in iron and lipid metabolism and its predisposition to oxidative insults, more and more studies have been conducted to explore the relationship between ferroptosis and various liver disorders, including nonalcoholic fatty liver disease (NAFLD). With increased morbidity and high mortality rates, NAFLD has currently emerged as a global public health issue. However, the etiology of NAFLD is not fully understood. In recent years, an accumulating body of evidence have suggested that ferroptosis plays a pivotal role in the pathogenesis of NAFLD, but the precise mechanisms underlying how ferroptosis affects NAFLD still remain obscure. Here, we summarize the molecular mechanisms of ferroptosis and its complicated regulation systems, delineate the different effects that ferroptosis exerts in different stages of NAFLD, and discuss some potential effective therapies targeting ferroptosis for NAFLD treatment, which putatively points out a novel direction for NAFLD treatment.